2022
DOI: 10.3390/cancers14020446
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-Associated Lymphoid Tissue (MALT) Lymphoma in the Gastrointestinal Tract in the Modern Era

Abstract: Extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) typically arises from sites such as the stomach, where there is no organized lymphoid tissue. Close associations between Helicobacter pylori and gastric MALT lymphoma or Campylobacter jejuni and immunoproliferative small intestinal disease (IPSID) have been established. A subset of tumors is associated with chromosomal rearrangement and/or genetic alterations. This disease often presents as localized disease, requiring diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 112 publications
(219 reference statements)
1
36
0
1
Order By: Relevance
“…This is further illustrated by the recent demonstration of constitutive mutations enhancing this pathway in patients with non-coeliac autoimmune enteropathies, who are also at risk of lymphomas 87. RCD2 and EATL also exemplify how the interplay between acquired somatic mutations and chronic inflammation driven by prolonged exposure to a luminal antigen can foster lymphomagenesis in the GI tract, a scenario already well established in mucosa-associated lymphoid tissue B lymphomas or in alpha chain immunoproliferative diseases 130…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This is further illustrated by the recent demonstration of constitutive mutations enhancing this pathway in patients with non-coeliac autoimmune enteropathies, who are also at risk of lymphomas 87. RCD2 and EATL also exemplify how the interplay between acquired somatic mutations and chronic inflammation driven by prolonged exposure to a luminal antigen can foster lymphomagenesis in the GI tract, a scenario already well established in mucosa-associated lymphoid tissue B lymphomas or in alpha chain immunoproliferative diseases 130…”
Section: Discussionmentioning
confidence: 88%
“… 87 RCD2 and EATL also exemplify how the interplay between acquired somatic mutations and chronic inflammation driven by prolonged exposure to a luminal antigen can foster lymphomagenesis in the GI tract, a scenario already well established in mucosa-associated lymphoid tissue B lymphomas or in alpha chain immunoproliferative diseases. 130 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut-associated lymphoid tissue (GALT) is known as the largest immunologic organ in the body and considerably contributes to the immune system of the whole body [ 9 ]. Intestinal MALToma is considered to develop from GALT, and the stomach is the most common site of intestinal lymphoma [ 10 ]. Excellent clinical outcomes have been achieved using EBRT in patients with gastric MALToma [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a large case analysis of colorectal MALT lymphoma reported that chemotherapy is most commonly performed for advanced disease. Chemotherapy is not recommended for patients with localized MALT lymphomas as these tumors are less responsive to standard chemotherapy than aggressive lymphomas[ 32 ]. Chemotherapy and/or immunotherapy is given when patients fail to respond to localized therapy or develop metastasis.…”
Section: Discussionmentioning
confidence: 99%